Nasal Delivery of Hesperidin/Chitosan Nanoparticles Suppresses Cytokine Storm Syndrome in a Mouse Model of Acute Lung Injury - Jin, Hua; Zhao, Zuguo; Lan, Qian; Zhou, Haotong; Mai, Zesen; Wang, Yuan; Ding, Xiaowen; Zhang, Wenting; Pi, Jiang; Evans, Colin E.; Liu, Xinguang (Frontiers in Pharmacology, 2021)
The cytokine storm or cytokine storm syndrome（CSS）was proved to be the leading cause of a high mortality induced by infectious diseases, such as Covid-19. There has not specific treatments for CSS and CSS induced acute respiratory distress syndrome (ARDS) so far. Thus, it is very urgent to develop effective drugs and therapeutic strategies to deal with this devastating syndrome. Nasal or inhale administration showed superiorities due to its efficient drug delivery to lungs. To improve the nasal mucosa absorption of poorly water-soluble drugs with poor mucosa bioavailability to a therapeutically effective level has attracted increasing interests. Here, chitosan nanoparticles loaded with hesperidin (HPD/CH/NPs) was developed for nasally delivery of anti-inflammation compound to inflammatory lungs. In vitro and in vivo, HPD/CH/NPs exhibited enhanced cellular uptake in the inflammatory microenvironment compared with free HPD. In a CSS mouse model, the HPD/CH/NPs markedly inhibited lung injury as evidenced by reduced inflammation cytokine level and vascular permeability compared with free HPD. Collectively, our study demonstrate nasal delivery of HPD/CH/NPs could significantly suppress the CSS in lungs, and nanoparticle-based Chinese medicine with anti-inflammation effects could be potentially used to reduce CSS in lungs induced by infectious diseases.